Development and Characterization of a 3D Printed Cocoa Bean Shell Filled Recycled Polypropylene for Sustainable Composites - Morales, María Alejandra; Maranon, Alejandro; Hernandez, Camilo; PORRAS HOLGUIN, ALICIA (Multidisciplinary Digital Publishing Institute - MDPI, 2021)
Natural filler-based composites are an environmentally friendly and potentially sustainable alternative to synthetic or plastic counterparts. Recycling polymers and using agro-industrial wastes are measures that help to achieve a circular economy. Thus, this work presents the development and characterization of a 3D printing filament based on recycled polypropylene and cocoa bean shells, which has not been explored yet. The obtained composites were thermally and physically characterized. In addition, the warping effect, mechanical, and morphological analyses were performed on 3D printed specimens. Thermal analysis exhibited decreased thermal stability when cacao bean shell (CBS) particles were added due to their lignocellulosic content. A reduction in both melting enthalpy and crystallinity percentage was identified. This is caused by the increase in the amorphous structures present in the hemicellulose and lignin of the CBS. Mechanical tests showed high dependence of the mechanical properties on the 3D printing raster angle. Tensile strength increased when a raster angle of 0° was used, compared to specimens printed at 90°, due to the load direction. Tensile strength and fracture strain were improved with CBS addition in specimens printed at 90°, and better bonding between adjacent layers was achieved. Electron microscope images identified particle fracture, filler-matrix debonding, and matrix breakage as the central failure mechanisms. These failure mechanisms are attributed to the poor interfacial bonding between the CBS particles and the matrix, which reduced the tensile properties of specimens printed at 0°. On the other hand, the printing process showed that cocoa bean shell particles reduced by 67% the characteristic warping effect of recycled polypropylene during 3D printing, which is advantageous for 3D printing applications of the rPP. Thereby, potential sustainable natural filler composite filaments for 3D printing applications with low density and low cost can be developed, adding value to agro-industrial and plastic wastes.

Los materiales compuestos a base de rellenos naturales son una alternativa ecológica y potencialmente sostenible a sus homólogos sintéticos o plásticos. El reciclaje de polímeros y el uso de residuos agroindustriales son medidas que ayudan a conseguir una economía circular. Así, este trabajo presenta el desarrollo y caracterización de un filamento para impresión 3D basado en polipropileno reciclado y cáscaras de habas de cacao, que aún no ha sido explorado. Los composites obtenidos fueron caracterizados térmica y físicamente. Además, se realizaron análisis morfológicos, mecánicos y del efecto de alabeo en las muestras impresas en 3D. El análisis térmico mostró una disminución de la estabilidad térmica cuando se añadieron partículas de cáscara de haba de cacao (CBS) debido a su contenido lignocelulósico. Se identificó una reducción tanto en la entalpía de fusión como en el porcentaje de cristalinidad. Esto se debe al aumento de las estructuras amorfas presentes en la hemicelulosa y la lignina del CBS. Los ensayos mecánicos mostraron una gran dependencia de las propiedades mecánicas del ángulo de trama de impresión 3D. La resistencia a la tracción aumentó cuando se utilizó un ángulo de trama de 0°, en comparación con las muestras impresas a 90°, debido a la dirección de la carga. La resistencia a la tracción y la deformación por fractura mejoraron con la adición de CBS en las muestras impresas a 90°, y se consiguió una mejor unión entre las capas adyacentes. Las imágenes de microscopio electrónico identificaron la fractura de partículas, la desvinculación entre el relleno y la matriz y la rotura de la matriz como los principales mecanismos de fallo. Estos mecanismos de fallo se atribuyen a la mala unión interfacial entre las partículas de CBS y la matriz, que redujo las propiedades de tracción de las muestras impresas a 0°. Por otro lado, el proceso de impresión demostró que las partículas de cáscara de haba de cacao reducían en un 67% el efecto de alabeo característico del polipropileno reciclado durante la impresión 3D, lo que resulta ventajoso para las aplicaciones de impresión 3D del rPP. De este modo, pueden desarrollarse filamentos compuestos de relleno natural sostenibles para aplicaciones de impresión 3D con baja densidad y bajo coste, añadiendo valor a los residuos agroindustriales y plásticos.
Keywords: Natural filled composites; 3D printing; Fused filament fabrication; Cocoa bean shell; Recycled polypropylene